(untitled) (Journal of the College of Languages (JCL), 2023)
The question of word–formation motivation is one of the most urgent problems of morphological features of diminutive vocabulary in the languages of different structures, Arabic – Semitic and Russian - Slavic. The relevance of this question lies in the fact that the analysis of morphological elements of word-formation motivation plays an important role not only in identifying formal and semantic connections between different units of the same language, but also has an applied value in the comparative study of different languages. Taking in to account that word-formation motivation is usually considered sequentially in order to identify motivational relationships of this type of vocabulary, we will study motivation in comparative analysis on the material of diminutive vocabulary of different languages. We will analytically approach the important question of the practical application of translation basics in achieving translation adequacy. Аннотация Вопрос о словообразовательной мотивации является одной из актуальных проблем, связанных с морфологическими особенностями диминутивной лексики в разноструктурных языках: арабском – семитском и русском – славянском. Анализ морфологических элементов словообразовательной мотивации играет большую роль не только в выявлении формально-семантических связей между разными единицами одного языка, но и имеет прикладное значение при сравнительном изучении разных языков. Учитывая, что словообразовательная мотивация, как правило, изучается последовательно, в рамках данного исследования рассмотрим ее на основе сравнительного анализа диминутивной лексики разных языков в целях выявления мотивационных отношений данного типа лексики, а также предпримем попытку аналитического подхода к вопросу о практическом применении переводческих основ при достижении адекватности перевода.